Rice Straw and Eggshell Ash as Partial Replacements of Cement in Concrete - Oliko, C.; Kabubo, C. K.; Mwero, J. N. (Engineering, Technology & Applied Science Research, 2020)
This paper presents the properties of concrete made with cement partially replaced with rice straw ash and eggshell ash. The rice straws and eggshells were incinerated, sieved, and ground, and the physical and chemical properties of the resultant ash and the other materials incorporated in the concrete mixes were determined. A class 35 concrete mix with no partial replacement of cement with rice straw ash designed with the British Research Establishment method with a water/cement ratio of 0.5 was considered as the control mix. The cement in concrete was partially replaced with rice straw ash by 5% to 30% and its compressive and splitting tensile strength was determined after 7, 14, 28, 56, and 90 days of curing. Durability, resistance to acid attack, and other wet and hardened properties of concrete with cement partially replaced with rice straw ash were also determined. An increase in compressive strength above the control mix was observed for concrete with 5% and 10% partial replacement of cement with rice straw ash. When eggshell ash was added to concrete mixes made with cement partially replaced with rice straw ash at 15% and 20%, the 28, 56, and 90-day compressive strength was found to increase. It can be concluded that rice straw and eggshell ash can be used to partially replace cement in concrete and result in a concrete whose properties compare favorably with control